The 22 July 2009 Total Solar Eclipse: Modeling D Region Ionosphere Using Narrowband VLF Observations. Issue 1 (22nd January 2019) - Venkatesham, K.; Singh, Rajesh; Maurya, Ajeet K.; Dube, Adarsh; Kumar, Sushil; Phanikumar, D. V.
Abstract: We present D region ionospheric response to 22 July 2009 total solar eclipse by modeling 19.8‐kHz signal from NWC very low frequency (VLF) navigational transmitter located in the Australia. NWC VLF signal was received at five stations located in and around eclipse totality path in the Indian, East Asian, and Pacific regions. NWC signal great circle paths to five stations are unique having eclipse coverage from no eclipse to partiality to totality regions, and the signal is exclusively confined in the low and equatorial regions. Eclipse‐induced modulations in NWC signal have been modeled by using long‐wave propagation capability code to obtain D region parameters of reflection height ( H ′) and sharpness factor ( β ). Long‐wave propagation capability modeling showed an increase in H ′ of about 2.3 km near central line of totality, 3.0 km in the region near to totality fringe, and 2.4 to 3.0 km in the region under partial eclipse. Using H ′ and β, Wait ionosphere electron density ( N e ) profile at the daytime altitude of 75 km showed a decrease in N e by about 58% at a station near totality central line, whereas at totality fringe and in partial eclipse region decrease in the N e was between 63% and 71% with respect to normal time values. The eclipse associated variations in the H ′, β, and N e are less in low‐latitude region as compared to midlatitude. The study contributes to explain observations of wave‐like signature in the D region during an eclipse and difference in the eclipse effect in the different latitude‐longitude sectors. Plain Language Summary: The work was taken up in light of recent 21 August 2017 great American total solar eclipse. An eclipse in magnitude larger than American eclipse happened on 22 July 2009 in Asia and Pacific region. We revisited our acquired very low frequency data to understand its effect on the ionized part of our upper space environment ionosphere, in low‐latitude region as 22 July 2009 eclipse happened in low‐latitude region. We performed long‐wave propagation capability modeling on the observed very low frequency transmission and compared results with the great total eclipse in midlatitude to high‐latitude regions. The results are unique and new and show that total eclipses have varied effect on D region ionosphere in different latitude‐longitude sectors of the globe. The unique results obtained show that for an eclipse in low latitudes, the variations in H ′ and β are more and D region N e reduction is less, when compared with eclipse in midlatitude region. Study contributes to explain observations of wave‐like signature in ionosphere during eclipse and difference in eclipse effect on ionosphere in different latitude‐longitude sector. Key Points: The decrease in NWC signal amplitude was observed at all five stations associated with 22 July 2009 total solar eclipse LWPC modeling showed an increase in the D region reflection height of about 2.3‐3.0 km at stations under varying eclipse conditions The decrease in electron density varied from 58% to 71% in the region from near central line of totality to region on the fringe of totality